PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS X DI SMKN 3 PADANG - Monita, Sri Devi; Mulyono, Heri; Devegi, Mourend (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
In the study of computer science, the use of learning aids is important. In Class X MPLB SMKN 3 Padang, information was obtained that there were several obstacles in the Computer Science learning process. These obstacles include the limited use of teaching materials, the materials used are only sourced from the internet and sometimes use presentation media. The research goal that is expected to be achieved by designing Android-based learning media for computer science subjects is to create valuable and practical learning media. This research method uses research and development (RD) methods. The results of the research The validity of the media content was 80.36% with the category "very valid", so it can be concluded that android-based learning media is suitable for use in the learning process by teachers and students. The results of the teacher's practice obtained a score of 95.14% with the category of "very practical", and from the practice of students obtained a score of 86.11% with the category of "very practical", so from the results of the responses of teachers and students it can be concluded that android-based educational media is suitable for use in the learning process at school.